2020
DOI: 10.2147/jmdh.s249664
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gamification for Diabetes Type 1 Management: A Review of the Features of Free Apps in Google Play and App Stores</p>

Abstract: The objective of this study was to review most of the existing free m-Health applications (Apps) that use the gamification approach to manage diabetes type 1 in both App and Google Play stores. Methods: Free mobile health applications "apps" that were related to diabetes mellitus have been identified in both App and Google Play stores. In order to cover all the mentioned applications, the following keywords, "game for type 1 diabetes" and "gamification for type 1 diabetes" were used in English and Arabic langu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…These authors suggested that the presence of a character in the application contributes to adherence to medication as well as to increase the blood glucose level readings [ 26 ]. Additionally, a recently published review showed that out of eight commercial-free applications, five of them used a character to be cared for by users (Commander Gage, Jerry the Bear, Pandabetic, Diapets, and Glucozor) [ 25 ]. As suggested by nearly a third of the caregivers, this feature was incorporated in the design of the screens of the gamified application proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors suggested that the presence of a character in the application contributes to adherence to medication as well as to increase the blood glucose level readings [ 26 ]. Additionally, a recently published review showed that out of eight commercial-free applications, five of them used a character to be cared for by users (Commander Gage, Jerry the Bear, Pandabetic, Diapets, and Glucozor) [ 25 ]. As suggested by nearly a third of the caregivers, this feature was incorporated in the design of the screens of the gamified application proposed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Stone suggested that the use of a friend challenge feature improves the self-management of diabetes condition through the competition concept [ 27 ]. It is pertinent to comment that no commercial application of the aforementioned literature review included a friend challenge function [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations